Upaya Perempuan Single Parent Dalam Mewujudkan Fungsi Keluarga Bagi Anak (Studi Kasus Di Kelurahan Jati, Kecamatan Mayangan, Kota Probolinggo) - Sugiarto, Tiara Syahani; Fida, Imanuddin Abil (Fakultas Syariah IAI Muhammadiyah Bima, 2022)
The family is the place where a person first learns the science of life before plunging into society. The government has regulated family functions in PP No. 87 of 2014 so that healthy and quality human and family resources can be created. However, the facts on the ground say that family integrity cannot be maintained forever. There are reasons for divorce or death that make a family lose one of the supports for the realization of a good family function. Separation with the condition that there are children in the results of a legal marriage makes a person have the status of a single parent. Even though the marital relationship has been broken, the function of the family for children must still be realized. This research will focus on examining the efforts made by single parent women in realizing family functions for children. How their understanding of family function will affect the level of success of a function in the family is realized. The efforts and obstacles they experience while being single parent women will also be examined in this study. By using an empirical approach that goes directly to the field and qualitatively descriptive data processing, it is found that the understanding of single parent women about family functions is very limited so that the realization of family functions according to the mandate of PP No. 87 of 2014 cannot be fully realized. The efforts and obstacles they encounter also depend on the age of the child, family conditions, and the reason for the separation.